(untitled) (Research, Society and Development, 2022)
The objective of this study was to conduct a survey of the analysis of the supply profile of the discipline of histology in Biological Sciences courses in public higher education institutions in the state of Paraíba. This is a cross-sectional, descriptive and quantitative study, carried out in the year 2022, based on data available on the websites of public higher education institutions in the state of Paraíba. Thus, for the analysis it was verified which institutions offer the discipline of Histology in the graduation course of Biological Sciences; for this, the curricular matrix of each course was observed. According to the research findings, there is a total of 17 Biological Science courses offered in the state of Paraíba, where all offer the discipline of histology with a workload variation between 30h and 67h. Thus, after the analyses, it can be concluded that most public higher education institutions in the state of Paraíba offer the discipline of histology in their curricula.